The solaria syndrome: social capital in a growing hyper-technological economy - Angelo Antoci; Fabio Sabatini; Mauro Sodini (Fondazione Eni Enrico Mattei (FEEM), 2010)
We develop a dynamic model to analyze the sources and the evolution of social participation and social capital in a growing economy characterized by exogenous technical progress. Starting from the assumption that the well-being of agents basically depends on material and relational goods, we show that the best-case scenarios hold when technology and social capital both support just one of the two productions at the expenses of the other. However, trajectories are possible where technology and social interaction balance one another in fostering the growth of both the social and the private sector of the economy. Along such tracks, technology may play a crucial role in supporting a 'socially sustainable' economic growth.
Keywords: O33; J22; O41; Z13; 330; Technology; Economic Growth; Relational Goods; Social Participation; Social Capital